RANCANG BANGUN APLIKASI HELP DESK BERBASIS WEB DI PT TRI STAR SURYA GEMILANG PURWOKERTO MENGGUNAKAN METODE DESIGN THINKING - Zuhrul Wafa; Muhamad Adito Pratama; M. Noviarsyah Dasaprawira (Universitas Methodist Indonesia, 2025)
This research aims to design and develop a web-based Help Desk application at PT Tristar Surya Gemilang Purwokerto using the Design Thinking method. The application is developed to improve efficiency and transparency in managing complaints, while accelerating problem resolution through an integrated system. The research follows four main stages: Empathize, Define, Prototype, and Testing, with a focus on addressing user needs to develop an effective solution. The results of Blackbox Testing show that the application meets the expected functionality for both admins and users, with features aligned with actual user needs. Key features tested include a secure login page, clear ticket data display, and an informative dashboard and reporting system. Figures 3 to 7 in the results show an intuitive user interface that ensures an efficient workflow. The system is expected to enhance the IT team’s performance in handling complaints and technical issues more efficiently, reduce communication errors between departments, and speed up problem resolution. The implementation of this system aims to improve productivity, operational effectiveness, and user satisfaction through better-managed complaint handling.